2015
DOI: 10.1093/nar/gkv885
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic factor EPC1 is a master regulator of DNA damage response by interacting with E2F1 to silence death and activate metastasis-related gene signatures

Abstract: Transcription factor E2F1 is a key regulator of cell proliferation and apoptosis. Recently, it has been shown that aberrant E2F1 expression often detectable in advanced cancers contributes essentially to cancer cell propagation and characterizes the aggressive potential of a tumor. Conceptually, this requires a subset of malignant cells capable of evading apoptotic death through anticancer drugs. The molecular mechanism by which the pro-apoptotic activity of E2F1 is antagonized is widely unclear. Here we repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 90 publications
3
52
0
Order By: Relevance
“…However, the apoptotic resistance to MEK inhibitors is one of the most difficult problems in the expansion of the indication for MEK inhibitors. Considering that we originally discovered these MEK inhibitors by screening for RB-reactivating compounds [ 33 ], it is no wonder that they cannot induce apoptosis well because RB activation restrains the pro-apoptotic activity of E2F1 [ 34 ]. We here demonstrated that the blockade of the mevalonate pathway using statins overcomes the apoptotic resistance to MEK inhibitors with suppression of Akt activation (Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the apoptotic resistance to MEK inhibitors is one of the most difficult problems in the expansion of the indication for MEK inhibitors. Considering that we originally discovered these MEK inhibitors by screening for RB-reactivating compounds [ 33 ], it is no wonder that they cannot induce apoptosis well because RB activation restrains the pro-apoptotic activity of E2F1 [ 34 ]. We here demonstrated that the blockade of the mevalonate pathway using statins overcomes the apoptotic resistance to MEK inhibitors with suppression of Akt activation (Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cisplatin treatment of cancer cell lines, such as SK-Mel-147 melanoma cells, resulted in upregulation of EPC1 , further pointing towards EPC1 enabling survival of cancer cells. Accordingly, knockdown of EPC1 led to increased DNA damage sensitivity and apoptosis in an E2F1-dependent mechanism (Wang et al 2016). …”
Section: From Basic Function To Translational Significancementioning
confidence: 99%
“…[11][12][13] To reconcile these contradictory observations, a common explanation is that the action of E2F1 depends on the cellular context, in terms of the presence or absence of differential cofactors, posttranslational modifications or state of other signaling pathways. [14][15][16][17][18][19] Another under-appreciated contribution, however, is the quantitative responses of individual cells to E2F1 levels. Expression levels of endogenous E2F1 can exhibit significant cell-cell variability, which is even higher for exogenous transgenes delivered, for example, via adenoviral transduction.…”
mentioning
confidence: 99%